2015
DOI: 10.1007/s40291-015-0154-3
|View full text |Cite
|
Sign up to set email alerts
|

Association of MDR1 Gene (C3435T) Polymorphism and Gene Expression Profiling in Lung Cancer Patients Treated with Platinum-Based Chemotherapy

Abstract: In conclusion, it is suggested that MDR1 TT genotypes had higher risk for the development of lung cancer. Also, this polymorphism could be used as a genetic marker for predicting the clinical outcome of lung cancer patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
10
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 22 publications
3
10
0
1
Order By: Relevance
“…Additionally, the risk of developing lung cancer was 5.78 times higher in the presence of the TT genotype of the studied polymorphism. These results are similar to those obtained by Subhani et al where TT genotype of SNP 3435 was associated with 5.23-fold higher risk of lung cancer development 26 . The obtained results are in contrast to those obtained by Sinues et al and Gervasini et al, where the relationship between polymorphism at position C3435T and the risk of developing lung cancer has not been demonstrated 27,28 .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Additionally, the risk of developing lung cancer was 5.78 times higher in the presence of the TT genotype of the studied polymorphism. These results are similar to those obtained by Subhani et al where TT genotype of SNP 3435 was associated with 5.23-fold higher risk of lung cancer development 26 . The obtained results are in contrast to those obtained by Sinues et al and Gervasini et al, where the relationship between polymorphism at position C3435T and the risk of developing lung cancer has not been demonstrated 27,28 .…”
Section: Discussionsupporting
confidence: 92%
“…On the other hand, in this study, the TT genotype in a subset of patients with G1 or G2 histologic malignancy of lung cancer (p = 0.0517) tends to occur more frequently, which is additionally confirmed by the result of the study for the mRNA expression of the ABCB1 gene, where it is demonstrated that the expression of mRNA is higher in the subgroup of patients with G1 or G2 (p = 0.0278). This dependence is confirmed by the results of the Subhani et al who also showed the correlation between the expression of ABCB1 and the intermediate degree of histological malignancy of the cancer 26 .…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…In the present study, we analyzed the effects of the C3435T and G2677T/A polymorphisms in the ABCB1 gene on the risk of developing bullous pemphigoid (BP) in a Polish population. Available data suggests that genetically determined P‐gp polymorphisms may predispose to the development of neoplasms, neurological disorders, and diseases of the gastrointestinal tract .…”
Section: Discussionmentioning
confidence: 99%
“…In dieser Studie haben wir bei einer polnischen Kohorte den Einfluss der C3435T‐ und G2677T/A‐Polymorphismen im ABCB1 ‐Gen auf das Risiko, an einem bulllösen Pemphigoid (BP) zu erkranken, analysiert. Die Daten legen nahe, dass genetisch determinierte P‐gp‐Polymorphismen die Entwicklung von Neoplasien, neurologischen und gastroenterologischen Erkrankungen begünstigen können .…”
Section: Diskussionunclassified